Factors Contributing to Massive Blood Loss on Peripartum Hysterectomy for Abnormally Invasive Placenta: Who Bleeds More? - Hironori Takahashi; Akihide Ohkuchi; Rie Usui; Hirotada Suzuki; Yosuke Baba; Shigeki Matsubara (Obstetrics and Gynecology International)
Introduction. To identify factors that determine blood loss during peripartum hysterectomy for abnormally invasive placenta (AIP-hysterectomy). Methods. We reviewed all of the medical charts of 11,919 deliveries in a single tertiary perinatal center. We examined characteristics of AIP-hysterectomy patients, with a single experienced obstetrician attending all AIP-hysterectomies and using the same technique. Results. AIP-hysterectomy was performed in 18 patients (0.15%: 18/11,919). Of the 18, 14 (78%) had a prior cesarean section (CS) history and the other 4 (22%) were primiparous women. Planned AIP-hysterectomy was performed in 12/18 (67%), with the remaining 6 (33%) undergoing emergent AIP-hysterectomy. Of the 6, 4 (4/6: 67%) patients were primiparous women. An intra-arterial balloon was inserted in 9/18 (50%). Women with the following three factors significantly bled less in AIP-hysterectomy than its counterpart: the employment of an intra-arterial balloon (4,448±1,948 versus 8,861±3,988 mL), planned hysterectomy (5,003±2,057 versus 9,957±4,485 mL), and prior CS (5,706±2,727 versus 9,975±5,532 mL). Patients with prior CS (−) bled more: this may be because these patients tended to undergo emergent surgery or attempted placental separation. Conclusion. Patients with intra-arterial balloon catheter insertion bled less on AIP-hysterectomy. Massive bleeding occurred in emergent AIP-hysterectomy without prior CS.